NATURE INSPIRED PRACTICES IN SUPER TALL BUILDING DESIGNS: SIMILARITIES OF FORM - Yıldız, Aslı; Avinç, Güneş Mutlu (My University, 2024)
Nowadays, competition between cities for super tall buildings is increasing. These buildings exceed the 300-meter height threshold, reaching enormous dimensions and playing a decisive role in the iconic character, visual impact, and prestige, and economic growth, technological and architectural progress of cities. In this context, the aim of the study is to formally analyze super tall buildings inspired by nature. In the study, which is evaluated according to two variables, super tall buildings are analyzed within the scope of the search for inspiration from nature in their form and interior formations. The study involves a content analysis of the ten tallest buildings in the Council on Tall Buildings and Urban Habitat (CTBUH) database. The formal analysis of the buildings revealed that the nature-inspired approach significantly influenced the design of the super tall buildings. This study emphasizes that combining super-tall designs with nature-inspired principles can create a new paradigm in architectural design. This combination improves the quality of life of individuals living in urban areas by enabling them to establish a closer relationship with nature. In this context, nature-inspired super tall buildings promote physical and mental well-being and create spaces that enhance indoor comfort.
Keywords: High-rise building; Super tall building; Nature inspired design; Formal analyses